С. ФЕРНЕ: ТРУДОВИЙ ПРИНЦИП І СУЧАСНЕ РЕФОРМУВАННЯ ШКОЛИ (Педагогіка вищої та середньої школи, 2008)
In the article paid a regard to labour principle of education of S. Frene. Recommendations are expressed in relation to the use of him at modern Ukrainian school.